Self-Lockdown - Pető, Andrea (Identities: Journal for Politics, Gender and Culture, 2020)
Author(s): Andrea Pető Title (English): Self-Lockdown Journal Reference: Identities: Journal for Politics, Gender and Culture Publisher: Institute of Social Sciences and Humanities - Skopje Page Range: 40-41 Page Count: 2 Citation (English): Andrea Pető, “Self-Lockdown,” Identities: Journal for Politics, Gender and Culture, Vol. 17, No. 1 (Summer 2020): 40-41.